PERANCANGAN DESAIN KARAKTER DALAM BUKU ILUSTRASI INTERAKTIF ‘MENARI DENGAN MUANG SANGKAL’ UNTUK ANAK USIA 9-12 TAHUN - Maslahah, Safira Andini; Pungky Febi Arifianto; Mahimma Romadhona (UNIVERSITAS STEKOM, 2025)
Madura Island has many uniqueness, not only in terms of its famous beach tourism but also in terms of its culture. One of them is the muang sangkal dance which is the culture of Sumenep Regency. However, the muang sangkal dance is less popular among 9-12 year olds than other traditional dances. To solve this problem, an interactive illustration book